6th IET International Conference on Power Electronics, Machines and Drives (PEMD 2012) 2012
DOI: 10.1049/cp.2012.0154
|View full text |Cite
|
Sign up to set email alerts
|

High reliability piezoelectric fan cooling for electric machine thermal management

Abstract: Electric machine thermal management is critical for the correct operation of high power density aerospace electrical machines. However, with increasing power density, a reliable, fault tolerant cooling mechanism needs to be developed. Piezoelectric fans are presented here as a potential, fault tolerant, forced cooling convective system that may further enhance the overall cooling of electric machines. Particle Image Velocimetry (PIV) techniques were implemented to map and quantify the flow fields generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The results in [21] demonstrated that the fins can neither be designed too thick nor too thin, because a large portion of the cooling channel is blocked in thick fins while thin fins will reduce the cross-sectional area available for air flow. Piezoelectric Fan Cooling was developed in [22,23], which indicated that an average convective heat transfer coefficient enhancement of 364.8% on the fin base and an enhancement of 53.6% on each of the fin side walls were attainable.…”
Section: Enclosed Housing Coolingmentioning
confidence: 99%
“…The results in [21] demonstrated that the fins can neither be designed too thick nor too thin, because a large portion of the cooling channel is blocked in thick fins while thin fins will reduce the cross-sectional area available for air flow. Piezoelectric Fan Cooling was developed in [22,23], which indicated that an average convective heat transfer coefficient enhancement of 364.8% on the fin base and an enhancement of 53.6% on each of the fin side walls were attainable.…”
Section: Enclosed Housing Coolingmentioning
confidence: 99%